PEMAHAMAN JEMAAT TENTANG KARUNIA BERNUBUAT BERDASARKAN 1 KORINTUS 14:3-5 - Cindy Veronika Sihombing; Rudyanto Chandra Saputra; Chandra Kirana Luhur (STT Kristus Alfa Omega, 2022)
The Holy Spirit is an instrument of power to carry out successfully the miraculous works and ministry of God's work in His church. The gift of prophecy in the church is motivated by the Holy Spirit, not primarily for prophesying the future, but is didactic in nature, namely to build believers' faith, spiritual life, and moral decisions to stay faithful to Christ and His teachings. This study aims to determine the level of understanding of the Bethel Tabernacle Church Shekinah Glory congregation about the gift of prophecy. In this study, researchers used quantitative methods by using a questionnaire. In this study, it is suspected that the congregation's understanding of the gift of prophecy based on 1 Corinthians 14:3-5 at the Bethel Tabernacle Shekinah Glory Church is not equal to or less than 50% of the maximum value. Based on the results of hypothesis testing with empirical calculations x 100%, the researchers found that the level of understanding of the congregation about the gift of prophecy based on 1 Corinthians 14:3-5 at the Bethel Tabernacle Shekinah Glory Church is in the very good category, which is 93%.Key Word:Â Congregation, Gift of the Holy Spirit, Gift of Prophecy